Idarucizumab in dabigatran-treated patients with acute stroke: a review and clinical update - Frol, Senta; Pretnar Oblak, Janja; Šabovič, Mišo; Ntaios, George; Kermer, Pawel (Frontiers in Neurology, 2024)
Idarucizumab is an antibody fragment specific for immediate reversal of dabigatran anticoagulation effects. Use of idarucizumab is approved for dabigatran-treated patients suffering from life-threatening or uncontrolled bleeding and those in need of urgent surgery or invasive procedures. Data from randomized controlled clinical trials and real-world experience provide reasuring evidence about the efficacy and safety of idarucizmab use in patients with acute stroke. In this narrative review, we summarize the available real-world evidence and discuss the relevance and importance of idarucizumab treatment in acute stroke patients in everyday clinical practice, also covering special issues like prothrombin complex concentrate application as alternative to idarucizumab, its application prior to endovascular therapy, the sensitivity of thrombi to lysis, as well as necessary laboratory examinations.